Unlocking Resilience: How Endurance Resistance Training Transforms Knee Cartilage in Young Male Rats - Kiran Yameen; Kevin Joseph Jerome Borges; Sumaira Imran Farooqui; Amna Aamir Khan; Syed Nudrat Nawaid Shah (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: This study examines how endurance resistance training affects the thickness of young male rats’ knee joint hyaline cartilage. These results can later be replicated for the benefit of humans, and an appropriate exercise-based plan can be designed accordingly. Methods: Twelve healthy young male rats were divided into an endurance exercise group (EG) and a sedentary control group (CG). The EG group climbed a ladder with weights, starting at 5% of their body weight and increasing to 40% over five weeks. Each session included 12-15 repetitions, 2-minute breaks, and lasted 30 minutes, five days a week.